A Multi-User Transradial Functional-Test Socket for Validation of New Myoelectric Prosthetic Control Strategies - Hansen, Taylor C.; Citterman, Abigail R.; Stone, Eric S.; Tully, Troy N.; Baschuk, Christopher M.; Duncan, Christopher C.; George, Jacob A. (Frontiers in Neurorobotics, 2022)
The validation of myoelectric prosthetic control strategies for individuals experiencing upper-limb loss is hindered by the time and cost affiliated with traditional custom-fabricated sockets. Consequently, researchers often rely upon virtual reality or robotic arms to validate novel control strategies, which limits end-user involvement. Prosthetists fabricate diagnostic check sockets to assess and refine socket fit, but these clinical techniques are not readily available to researchers and are not intended to assess functionality for control strategies. Here we present a multi-user, low-cost, transradial, functional-test socket for short-term research use that can be custom-fit and donned rapidly, used in conjunction with various electromyography configurations, and adapted for use with various residual limbs and terminal devices. Participants with upper-limb amputation completed functional tasks in physical and virtual environments both with and without the socket, and they reported on their perceived comfort level over time. The functional-test socket was fabricated prior to participants’ arrival, iteratively fitted by the researchers within ten minutes, and donned in under one minute (excluding electrode placement, which will vary for different use cases). It accommodated multiple individuals and terminal devices and had a total cost of materials under $10 USD. Across all participants, the socket did not significantly impede functional task performance or reduce the electromyography signal-to-noise ratio. The socket was rated as comfortable enough for at least two hours of use, though it was expectedly perceived as less comfortable than a clinically-prescribed daily-use socket. The development of this multi-user, transradial, functional-test socket constitutes an important step towards increased end-user participation in advanced myoelectric prosthetic research. The socket design has been open-sourced and is available for other researchers.